Kurikulum Berbasis Vokasional Dalam Membentuk Jiwa Entrepreneurship Islami Peserta Didik - Mardiana, Binti Ulfa; Riyadi, Ahmad Ali (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
This research focuses on designing, implementing, and evaluating a vocational-based curriculum in shaping the Islamic entrepreneurship spirit of class X students at MAN 1 Nnganjuk in the 2021/2022 school year. This research uses a qualitative approach. This research type is a case study, where the data is taken through interviews, field notes, records, photos, personal documents, etc. The results showed that the vocational-based curriculum in shaping the Islamic entrepreneurship spirit of students is contained in the following steps: (1) vocational-based curriculum design through skills programs at Madrasah Aliyah Negeri (MAN) 1 Nganjuk is to place its students in a central position (learner-centered-design) which in its implementation is based on experience or activities (activity/experience design). (2) From the results of the research data analysis, it is seen that the madrasah's efforts in shaping the spirit of Islamic entrepreneurship are to integrate the content of vocational program subjects, which include; Visual communication design (DKV), culinary, beauty, fashion, batik craft, and automotive with workshop and entrepreneurship subjects, and supported by religious material fiqh muamalah which has been taught in class X, where curriculum evaluation activities are carried out by the madrasah head and the vocational curriculum development team every time they start a new semester with a coordination meeting, while for vocational learning evaluation of students is carried out formatively (daily) and summatively (end of semester/end of the year assessment). With the various steps applied in the vocational curriculum, it is hoped that the character of students with an entrepreneurial spirit is formed with the characteristic of prioritizing Islamic values or what is commonly called Islamic entrepreneurship.